public policies as a factor of gentrification and urban renewal in the santa Inés Neighborhood of Bogotá, sector called the Bronx. (2017)
The research carried out in the Santa Ines neighborhood adjacent to La Candelaria, Bogotá's historic center seeks to analyze how, as a result of the desire to renew the urban space through the application of public policies and to eradicate the delinquency bands that operated in the sectro of the Bronx , There was the process of gentrification of a population category recognized until recently as "inhabitant of the street", which arises from the observation of the events that occurred after the expulsion of its inhabitants in May 2016, which today after a Year shows us the worrisome situation of these human beings in the majority dispersed by the city, it is to recognize that the local authority offered refuge and treatment to these people but only a small part has taken advantage of these benefits, In fact, policies were short because they did not categorically categorize their population, much less offer the solution required by them. The methodology used and the sources of information used to address the problem are the result of the application of qualitative research techniques using document analysis, analysis of the Territorial Planning Plan, the value of the soil represented in the cadastral updating studies , And photographic records among others. An important aspect of the research lies in the fact of concatenating the concepts of urban renewal and gentrification associated with the territory.